2009
DOI: 10.1073/pnas.0914140107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of active targeting in solid tumors with transferrin-containing gold nanoparticles

Abstract: PEGylated gold nanoparticles are decorated with various amounts of human transferrin (Tf) to give a series of Tf-targeted particles with near-constant size and electrokinetic potential. The effects of Tf content on nanoparticle tumor targeting were investigated in mice bearing s.c. Neuro2A tumors. Quantitative biodistributions of the nanoparticles 24 h after i.v. tail-vein injections show that the nanoparticle accumulations in the tumors and other organs are independent of Tf. However, the nanoparticle localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
429
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 624 publications
(466 citation statements)
references
References 25 publications
21
429
1
Order By: Relevance
“…However, if the receptor density is such that multiple targeting ligands on the nanoparticle can bind to the receptors simultaneously, then the targeted nanoparticle avidity (9) and selectivity (8) can be increased. These effects have been illustrated in several investigations; for example, Choi et al (9) reported the interactions of Tf-containing gold nanoparticles on both cancer cells in vitro and tumors in vivo in mice. These authors showed that the animal whole-body biodistribution of Tf-containing gold nanoparticles of ∼70 nm in diameter was independent of the Tf content, but that the amount of nanoparticles localizing in the cancer cells of solid tumors at 24 h after injection increased with increasing Tf content.…”
mentioning
confidence: 99%
“…However, if the receptor density is such that multiple targeting ligands on the nanoparticle can bind to the receptors simultaneously, then the targeted nanoparticle avidity (9) and selectivity (8) can be increased. These effects have been illustrated in several investigations; for example, Choi et al (9) reported the interactions of Tf-containing gold nanoparticles on both cancer cells in vitro and tumors in vivo in mice. These authors showed that the animal whole-body biodistribution of Tf-containing gold nanoparticles of ∼70 nm in diameter was independent of the Tf content, but that the amount of nanoparticles localizing in the cancer cells of solid tumors at 24 h after injection increased with increasing Tf content.…”
mentioning
confidence: 99%
“…In order to avoid the rapid removal of these nanoparticles from systemic circulation after intravenous administration, due to rapid uptake by reticular endothelial system (RES), pegylated PPSu nanoparticles based on PEG-PPSu copolymers have been developed [11][12][13][14][15][16][17][18]. Although pegylation of nanoparticles surface can lead to their preferential accumulation in tumor tissue due to the enhanced permeability and retention (EPR) phenomenon, it does not appear to increase the uptake of nanoparticles, and consequently of their drug load, by cancer cells [19]. In order to enhance nanoparticles uptake by tumor cells, targeting moieties, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…nanoliposomes | PLK-1 inhibitor | MEK-1 inhibitor T here is currently wide interest in the development of nanoparticles for drug delivery (1)(2)(3)(4)(5)(6)(7). This area of research is particularly relevant to cancer drugs, wherein the therapeutic ratio (dose required for effectiveness to dose causing toxicity) is often low.…”
mentioning
confidence: 99%